The Role of Mohammad Ichsan in Indonesian Foreign Diplomacy 1945-1960 - Ihzanda Shibawati; Ibnu Sodiq (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study aims to analyze the role of Mohammad Ichsan in Indonesia's foreign diplomacy during the early years of independence. The study is motivated by the tendency of Indonesian diplomatic historiography to focus primarily on major figures such as Soekarno and Mohammad Hatta, while the contributions of other diplomats like Mohammad Ichsan have received far less scholarly attention. This research employs the historical method with a descriptive qualitative approach, following the stages of heuristics, verification, interpretation, and historiography. The sources used in this study include archival documents, photographic archives, and relevant secondary literature. The findings indicate that Mohammad Ichsan did not merely perform administrative duties as a diplomat but also served as a symbolic representative of the state, an actor in socio-cultural diplomacy, and part of the institutional consolidation of Indonesian diplomatic missions abroad. Through various diplomatic and ceremonial activities in Bangkok, he contributed to affirming the presence and legitimacy of the Republic of Indonesia in the international arena. This study highlights the importance of supporting diplomats in the practice of Indonesian diplomacy in the post-independence period.